The Role of Networks, Global Collaboration, Diaspora, and Associations in Encouraging the Internationalization of MSMEs (Case Study on Kendang Jimbe MSMEs, Sentul, Blitar, East Java) - Suprianto Suprianto; Sudarmiatin; Heri Pratikto (Kirana Publisher (KNPub), 2026)
This study aims to analyze the role of business networks, global collaboration, diaspora, and associations in driving the internationalization process of MSMEs, particularly in the jimbe drum craft MSME in Sentul Village, Blitar. The approach used is qualitative with a case study method, through in-depth interviews, observation, and documentation. The results are expected to show that business networks have a strategic role in opening international market access, global collaboration increases efficiency and product innovation, diaspora functions as a bridge connecting foreign markets, and business associations strengthen the capacity and competitiveness of MSMEs. The synergy of these four factors is key to improving export performance and business sustainability in the global market.